A Passion of Gold and Fire - Sebastien, Pins (Belgium, 2015)
The head of an apiary school, nearing the end of his career, worries there's no one to carry on his work with bees.
Duration: 00:06:00
Verzio Film Festival Submission
Keywords: Documentary films